Beyond the Mevalonate Pathway: Control of Post-Prenylation Processing by Mutant p53 - Borini Etichetti, Carla M; Arel Zalazar, Evelyn; Cocordano, Nabila; Girardini, Javier (Frontiers in Oncology, 2020)
Missense mutations in the TP53 gene are among the most frequent alterations in human cancer. Consequently, many tumors show high expression of p53 point mutants, which may acquire novel activities that contribute to develop aggressive tumors. An unexpected aspect of mutant p53 function was uncovered by showing that some mutants can increase the malignant phenotype of tumor cells through alteration of the mevalonate pathway. Among metabolites generated through this pathway, isoprenoids are of particular interest, since they participate in a complex process of postranslational modification known as prenylation. Recent evidence proposes that mutant p53 also enhances this process through transcriptional activation of ICMT, the gene encoding the methyl transferase responsible for the last step of protein prenylation. In this way, mutant p53 may act at different levels to promote prenylation of key proteins in tumorigenesis, including several members of the RAS and RHO families. Instead, wild type p53 acts in the opposite way, downregulating MVA pathway genes and ICMT. This oncogenic circuit also allows to establish potential connections with other metabolic pathways. The demand of acetyl-CoA for the MVA pathway may pose limitations in cell metabolism. Likewise, the dependence on S-adenosyl methionine for carboxymethylation, may expose cells to methionine stress. The involvement of protein prenylation in tumor progression offers a novel perspective to understand the antitumoral effects of mevalonate pathway inhibitors, such as statins, and to explore novel therapeutic strategies.